Scheme for sub-shot-noise transmission measurement using a time-multiplexed single-photon source - Magnoni, Agustina Gabriela (2021)
Sub-shot-noise performance in transmission measurements can be achieved in optical quantum metrology owing to significantly lower uncertainty in light intensity of quantum beams compared to their classical counterparts. In this work, we simulate the outcome of an experiment that uses a multiplexed single-photon source, considering several types of experimental losses, where we show that the sub-Poissonian statistics of the output is key for achieving sub-shot-noise performance. We compare the numerical results with the shot-noise limit attained using coherent sources and the quantum limit, obtained with an ideal photon-number Fock state. We also investigate conditions in which threshold detectors can be used, as well as the effect of input light fluctuations. Our results show that sub-shot-noise performance can be achieved with improvement factors ranging from 1.5 to 2, even without using number-resolving detectors.